New method for estimating the grounding reliability test of aircraft cable shield - Hongxu Zhao; Geng Zhang; Yongyun Wang; Qian Wang (Functional Materials, 2017)
We investigated a new method based on electromagnetic induction technique is proposed for reliability test of the grounding connection, and a test setup is built for experiment. As proven by the experimental results, the proposed method can provide a wide measurement rang and sufficiently high accuracy, to measure the loop resistance and joint resistance.